Surgical treatment of traumatic frontal hematoma: comparison of the endoscopic supraorbital approach with frontotemporal approach - Yang, Qiang; Cui, Min; Xiong, WeiMing; Wang, YangLingXi; Liu, Yang; Zhou, WeiDuo; Chen, Peng; Tang, XiaoYong (Frontiers in Neurology, 2023)
Background The objective of this study was to compare the efficacy, safety, and outcomes of the endoscopic supraorbital approach and frontotemporal approach for the treatment of traumatic frontal hematoma, with the aim of demonstrating the feasibility of the endoscopic supraorbital approach. Methods A total of 24 cases underwent hematoma evacuation, including 10 cases using the endoscopic supraorbital approach and 14 cases using the frontotemporal approach. Baseline demographic data, hematoma clearance rate, blood loss, postoperative complications, and 6-month outcomes were retrospectively analyzed. Results Both approaches effectively evacuated the hematoma, with hematoma clearance rates of 90.97 ± 10.23% in the endoscopic supraorbital group and 85.29 ± 16.15% in the frontotemporal approach group (p > 0.05). The supraorbital approach group demonstrated significantly shorter operation times compared to the frontotemporal approach group (116.50 ± 28.19 min vs. 193.29 ± 72.55 min, p < 0.05), as well as significantly less blood loss (55.00 ± 33.08 mL vs. 685.71 ± 840.20 mL, p < 0.05). There was no significant difference in the rate of postoperative complications between the two groups, and the majority of patients achieved favorable outcomes with a Glasgow Outcome Scale score of 4 or 5 in both groups. Conclusion Compared to the frontotemporal approach, the endoscopic supraorbital approach offers advantages such as shorter operation times, reduced blood loss, similar treatment effects, and comparable complication rates. Therefore, the endoscopic supraorbital approach may serve as a viable alternative for the treatment of traumatic frontal hematoma.